Upaya Penanggulangan dan Pencegahan Penyakit HIV/AIDS Bagi Masyarakat di Desa Bungkuk - Andhita Risko Faristiana; Haifa Oktafiana; Hertina Sari Widarto; Qurroti Akyunina (Pusat Riset dan Inovasi Nasional, 2023)
HIV/AIDS is an infectious disease that continues to be a concern in Indonesia and other countries in the world. According to information from officials in Bungkuk Village, there are three people affected by HIV/AIDS. This writing aims to provide socialization of understanding about the prevention of HIV / AIDS for the people in Bungkuk Village. The service method applied in that is asset-based and surrounding potential in the community or known as Asset-Based Community Development (ABCD). The ABCD method has five stages including: discovery, dream, design, define, and destiny. The result of the socialization carried out was an understanding regarding the information provided which was acceptable to the participants as evidenced by the discussion which went quite smoothly and the participants were quite enthusiastic about this socialization. This socialization is useful to make people aware of the dangers of HIV/AIDS for the health of the human body.